Effect of IBA concentration on Rooting and Seedling growth of Fig ( Ficus carica L.)varieties (waziri and Aswad Diyala) - Altememy, Harith Mahmood Azeez (Journal of Kerbala for Agricultural Sciences, 2015)
The experiment was conducted in the lath house, College of Agriculture / University of Karbala for the period from mid-February until July 2013. The aim is to study the effect of different concentrations of the IBA on the percentage of rooted cuttings, vegetative and root characteristics of fig varieties; Waziri and Aswad Diyala. Four IBA concentrations were used (0, 1000, 2000 and 3000 mg/L ). Randomized complete Block Design (R.C.B.D) was used with three replicates and 10 cuttings for each replicates . The results showed that Waziri gave asignificant increase in (the rooting percentage, shoots length and dry weight of vegetative and roots) over the Aswad Diyala . The result also showed that cuttings treated with IBA at a concentration of (3000 mg/L) increased, significantly the rooting percentage, shoots length, number and length of roots and dry weight of vegetative and roots) comparing with other concentrations. The interaction of both varieties with IBA treatments showed a significant difference in (the rooting percentage Shoots length, number and length of roots, dry weight of vegetative and roots) over the control treatment, but the cultivar waziri treated with IBA at a concentration of ( 3000 mg. /L) gave the highest results.